"Do the Things You're Gonna Do on Game Day, Just Don't Get Hurt": A Narrative Analysis of the NFL's "Future of Football" Advertising Campaign. Issue 1 (1st January 2022) - Bell, Travis R.; Applequist, Janelle
ABSTRACT: This study explores the NFL's "Future of Football" advertising campaign as a narrative strategy embedded within the league's tradition focused on brand control. Using narrative and thematic analyses, 17 broadcast advertisements that aired from 2016–2019 are examined to investigate the league's re-implementation of media messaging to position itself as a leader on safety. Findings indicate a narrativization of the NFL as a bastion of scientific discovery aimed at improving the safety of football, whereby science is manipulated under the guise of technology and innovation (e.g., new helmets and equipment), and player agency is orchestrated to parrot the NFL's brand messaging.